Power and Resource Allocation for Orthogonal Multiple Access Relay Systems. (13th October 2008) - Mesbah Mesbah, Wessam Wessam; Davidson Davidson, Timothy N. Timothy N.
Abstract : We study the problem of joint power and channel resource allocation for orthogonal multiple access relay (MAR) systems in order to maximize the achievable rate region. Four relaying strategies are considered; namely, regenerative decode-and-forward (RDF), nonregenerative decode-and-forward (NDF), amplify-and-forward (AF), and compress-and-forward (CF). For RDF and NDF we show that the problem can be formulated as a quasiconvex problem, while for AF and CF we show that the problem can be made quasiconvex if the signal-to-noise ratios of the direct channels are at least− 3  dB. Therefore, efficient algorithms can be used to obtain the jointly optimal power and channel resource allocation. Furthermore, we show that the convex subproblems in those algorithms admit a closed-form solution. Our numerical results show that the joint allocation of power and the channel resource achieves significantly larger achievable rate regions than those achieved by power allocation alone with fixed channel resource allocation. We also demonstrate that assigning different relaying strategies to different users together with the joint allocation of power and the channel resources can further enlarge the achievable rate region.